Steady-state spectroscopy to single out the contact ion pair in excited-state proton transfer - Grandjean, Alexander; Pérez Lustres, José Luis; Muth, Stephan; Maus, Daniel; Jung, Gregor (The journal of physical chemistry letters, 2021)
Despite the outstanding relevance of proton transfer reactions, investigations of the solvent dependence on the elementary step are scarce. We present here a probe system of a pyrene-based photoacid and a phosphine oxide, which forms stable hydrogen-bonded complexes in aprotic solvents of a broad polarity range. By using a photoacid, an excited-state proton transfer (ESPT) along the hydrogen bond can be triggered by a photon and observed via fluorescence spectroscopy. Two emission bands could be identified and assigned to the complexed photoacid (CPX) and the hydrogen-bonded ion pair (HBIP) by a solvatochromism analysis based on the Lippert-Mataga model. The latter indicates that the difference in the change of the permanent dipole moment of the two species upon excitation is ∼3 D. This implies a displacement of the acidic hydrogen by ∼65 pm, which is in quantitative agreement with a change of the hydrogen bond configuration from O-H···O to -O···H-O+.
Gesehen am 09.09.2021